DISTILLATION OF BINARY TWO-PHASE MIXTURES WITH VARIOUS PHYSICO-CHEMICAL PROPERTIES: NORMAL MODE AND DEVIATIONS FROM IT - L. A. Serafimov; K. A. Morozov (Тонкие химические технологии, 2016)
In this article, the normal continuous mode of distillation is considered using an example of binary two-phase mixture distillation. In practice, there are often deviations from the normal mode. It has been proved that the deviation leads to an increase in energy consumption for the ongoing process. In the industry, columns separating binary mixtures are normally the finishing apparatuses in the flow-sheet separation of multicomponent mixtures, which are obtained in the reactor as a result of main reactions as well as by-reactions. The distillation of binary mixtures is relatively simpler than that of multicomponent mixtures. In this regard, the fundamental parts of monographs especially in the thirties-forties of the last century started with the study of binary mixtures, although multicomponent mixtures were the main focus. The aim of analyzing this complex and the highly energy-intensive process is to facilitate the choice of a mathematical model for the process and the determination on its basis variance. Variance is a set of independent variables that allow calculation of a process only after taking into account the number of independent equations related to these variables. A case of deviation from the normal distillation regime where an under-heated liquid enters the column feed has been revised. This leads to an increase in energy consumption during distillation. Key indicators of the normal regime relative to the level of feed and the temperature of the liquid are shown in the text.